P 91 Changes of cerebral perfusion and cerebral pressure induced by rapid altitude changes of 1000 m in an alpine region? – results of a neurosonographic study of volume flow rate and optic sheath diameter. Issue 10 (October 2017) - Eicke, M.; von Brentano, S.; Mark, T.
Abstract : Background: As the clinical implications of altitude sickness are well known, the etiology of this potential life threatening disease is far from understood completely. We studied noninvasively by means of Neurosonography the effects of a rapid change of altitude in the alpine region on the cerebral volume flow and intracranial pressure. Methods: We studied 36 participants (19 m, 17 w; mean age 52 yrs) of the 55th. Conference of Clinical Neurophysiology and Adjacent Specialities, which took place in January 2016 in Gaschurn/Montafon/Austria. Participants were studied first in the conference hotel (altitude above sea level appr. 1000 m) and with a maximum latency of 30 min. to the first study a second time in a mountain station (altitude appr. 2000 m). The primary question of this trial was to investigate a potential altitude change induced impact on the volume flow rate in the Common Carotid (CCA) and Internal Carotid Artery (ICA) as well as flow velocity changes in the Middle Cerebral Artery (MCA). Additionally the Optic Sheath Diameter (OSD) was determined to obtain data on intracranial pressure. The extracranial volume flow rate was determined by integrating vessel diameter and flow velocity information. Data were obtained by 2 portable color duplex systems (GE, Logiq e; 3–10 (Doppler 5) MHz linear array probe for extracranial applications and OSD measurements; a 1, 7-4 (Doppler 2, 5) MHz phased array probe was applied transcranially). Additionally, data on blood pressure, heart rate, facial skin temperature and endexpiratory CO2 were obtained. Results: As the volume flow rate in the CCA significantly dropped from 508 to 410 ml/min. Discussions/Conclusions: Previous neurophysiological studies on altitude sickness as published from the Inselspital in Bern/Switzerland have focussed on extreme situations, mountaineers are exposed in extreme high altitude (including the Himalaya). We studied moderate, but rapid changes of altitude. The study set up was applied successfully and can also be used in future studies investigating bigger altitude changes. An altitude change of 1000 m, which skiers and conventional European mountaineers are experiencing, has no impact on cerebral perfusion and intracranial pressure.